2000
DOI: 10.1111/1467-6494.00119
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Factor Model of Trait Anger: Dimensions of Affect, Behavior, and Cognition

Abstract: The structure of trait anger was tested in a study of 24 self-report scales. Exploratory factor analyses in an undergraduate sample (N = 457) yielded a two-factor model (comprising cynicism and aggression) and a three-factor model (representing angry emotions, aggressive behaviors, and cynicism). Subsequent evaluations, including confirmatory factor analyses, indicated that the three-factor model provided the best characterization of the trait anger domain. The three-factor solution was consistent with an "ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
163
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 42 publications
21
163
1
2
Order By: Relevance
“…Although the developmental literature does not tend to use self-report measures to assess personality, it has been suggested that effortful control is an important precursor to adult levels of trait agreeableness (Ahadi & Rothbart, 1994;Cumberland-Li, Eisenberg, & Reiser, 2004;Kochanska & Knaack, 2003). This suggestion is consistent with data indicating that both effortful control (Calkins, Gill, Johnson, & Smith, 1999) and agreeableness (Martin, Watson, & Wan, 2000) are inversely related to anger and aggression.If effortful control is a substantial precursor of agreeableness, then the developmental literature makes some other points that deserve more systematic attention. First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Although the developmental literature does not tend to use self-report measures to assess personality, it has been suggested that effortful control is an important precursor to adult levels of trait agreeableness (Ahadi & Rothbart, 1994;Cumberland-Li, Eisenberg, & Reiser, 2004;Kochanska & Knaack, 2003). This suggestion is consistent with data indicating that both effortful control (Calkins, Gill, Johnson, & Smith, 1999) and agreeableness (Martin, Watson, & Wan, 2000) are inversely related to anger and aggression.If effortful control is a substantial precursor of agreeableness, then the developmental literature makes some other points that deserve more systematic attention. First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation.…”
supporting
confidence: 56%
“…One perspective extends agreeableness to the self-regulation of hostile thoughts and feelings. It is clear that agreeableness is inversely related to self-report scales tapping hostile thoughts, feelings, and behaviors (Martin et al, 2000). Moreover, agreeable individuals have been found to be less susceptible to the influence of accessible hostile thoughts in a number of social cognitive paradigms (e.g., .…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al advocate for the standardization of these concepts emphasizing that anger corresponds to affect, aggression to behavior, and hostility (or cynicism) to cognition. Together the three constructs form a three-factor "ABC" model of trait anger (Martin, Watson et al 2000).…”
Section: The MIX Of Concepts: Hostility Anger Aggression and Other mentioning
confidence: 99%
“…Martin et al advocate for the standardization of these concepts emphasizing that anger corresponds to affect, aggression to behavior, and hostility (or cynicism) to cognition. Together the three constructs form a three-factor "ABC" model of trait anger (Martin, Watson et al 2000).Aside from hostility, anger and aggression, VE and distressed personality are more complex concepts. Although they overlap partially, these constructs include specific patterns and aspects not captured by general scales for hostility, anger and aggression.…”
mentioning
confidence: 99%
“…There are good reasons for possessing this knowledge. The warmth-coldness dimension is a primary predictor of relationship quality (Markey & Markey, 2007), personality disorders (Locke, 2006), aggressive behavior (Martin, Watson, & Wan, 2000), criminality (Edens, 2009), and lack of social support (Smith, Traupman, Uchino, & Berg, 2010). …”
mentioning
confidence: 99%